Challenging male dominance through the substantive representation of women: the case of an online women's mentoring platform. (25th June 2020) - Durbin, Susan; Lopes, Ana; Warren, Stella
Abstract : This article analyses the design of an online mentoring platform—for women by women—in a high‐technology, male‐dominated UK industry: aviation and aerospace. Based on interviews with professionals and managers, we analyse the journey of the women involved and contribute to the understanding of the role of women (individually and collectively) in challenging gendered norms in a male‐dominated industry through the theoretical lenses of 'critical actors' and 'critical mass'. We combine these concepts, usually seen as mutually exclusive, to explain the success of the online platform. We show how a small number of self‐selected critical actors represented, listened and responded to the needs of the women in their industry, thus achieving the substantive representation of women. We also argue that while critical actors were key to its inception, the mentoring platform now needs a critical mass of women to ensure its success.